Factors influencing the acquisition of employability skills by students of selected technical secondary school in Malaysia - Danial, Jovinia; Bakar, Ab. Rahim; Mohamed, Shamsiah (Canadian Center of Science and Education, 2014)
The main purpose of the study was to assess the acquisition of employability skills by vocational students in Malaysia. A total of 214 students participated in the study. We used the SCANS instrument to assess vocational students’ employability skills. The overall mean of vocational secondary students’ employability skills was 3.81 (SD = 0.34). Students’ employability skills were found to be correlated with gender (rpb = -.172, p = .012), industrial training (rpb = .137, p = .046), involvement in extracurricular activities (r = .177, p = .010), participation in career development activities (r = .218, p = .001) and self-concept (r = .429, p = .000). We used a step-wise multiple regression to determine the variables that best predict students’ acquisition of employability skills. We found that three variables (self-concept, participation in career development activities, and industrial training) explained 23.1% of the total variance in the acquisition of employability skills, with self-concept being the main predictor (B = 0.39), followed by participation in career development activities (B = 0.29), and industrial training (B = 0.19).